The Role Of Health Knowledge And Awareness In Preventing Parasitic Infections Among Smokers And Non-Smokers In Babylon (International Journal of Environmental Sciences, 2025)
Background: Parasitic diseases remain a public health concern, especially among populations with varying health awareness and health knowledge. It is essential to know the impact of health knowledge and sources of information on the occurrence of parasitic diseases to effectively implement preventive measures.Aim of study: To examine the role of health awareness and knowledge and sources of information, in preventing parasitic infection among Babylonian smokers and non-smokers.Methodology: The research was a descriptive cross-sectional study conducted from November 1, 2024, to January 1, 2025, at Imam Al-Sadiq Hospital and Morjan Medical City in Babylon Province. 125 participants who were selected by purposive sampling and tested positive or negative for intestinal parasitic infections and consented to participate were included. The data were collected by administering a validated structured questionnaire on sociodemographic variables, smoking status, knowledge about parasitic infections, and information sources. The infection status was assessed by the results of stool examination. The data were analyzed using IBM SPSS version 23, with descriptive statistics and chi-square tests to find associations.Results: The study showed that there was a very high correlation between knowledge regarding parasitic infection rates and health. Out of the knowledgeable participants, 82.4% were infected, whereas 17.6% of those with no knowledge were infected (P = 0.00007). The rate of infection also varied based on the source of knowledge, with the maximum rate of infection among those who reported doctors as the source of information (39.2%) and the lowest rate of infection in those who used other sources (4.8%) (P = 0.00001). Further, 97.6% of those who had no infection, and 54.5% and 53.1% of participants with parasitic and microscopic infection, respectively, belonged to the knowledgeable group in comparison with 2.4% and 45.5% belonging to the no-knowledge group (P = 0.00006). Based on the source of knowledge, the infection type also varied significantly, with the internet and doctors showing lower rates of infection.Conclusion: Increased awareness regarding health and credible sources of information, particularly health staff, are linked with less parasitic infection. Increased awareness of health via credible channels is the solution to the success of prevention and control of parasitic infection in smokers and non-smokers in Babylon.